Collection biases in aquatic macrophytes in Brazil: a case study with duckweed (Lemnoideae, Araceae) - Fabiane Barral Sampaio; Marco Octávio de Oliveira Pellegrini; Guilherme Sampaio Cabral; Ana Luisa Biondi Fares; Vali Joana Pott; Ely Simone Cajueiro Gurgel; Thaisa Sala Michelan (Rodriguésia)
Abstract Lemnoideae species (duckweed) are the smallest angiosperms in the world and typically associated with lentic environments. The challenges in collecting this group and the limited number of studies on this family result in a low number of Lemnoideae records. In this study, we summarize the studies published in Brazil on Lemnoideae to understand the gaps and advances in the research of this group. Information on herbarium records in online databases were gathered in a single matrix to analyze the collection gaps of this group in Brazil. In total, 1,019 records of Lemnoideae were obtained, coming from 22 states, five regions, and six biomes. The largest number of records was found in the Center-West and Northeast regions, areas with a greater sampling effort and higher number of specialists in the group. In contrast, the North Region had a low number of records. This is a reflection of a lack of funding in some regions as well as of botanical blindness that limit the knowledge about the ecological potential of this group and hinder its identification. Thus, there is a clear distribution gap in the knowledge and collections of duckweed in Brazil, underscoring the need to intensify the collection efforts in under sampled areas in order to achieve a more accurate mapping of this group’s diversity in the country.